2019
DOI: 10.1590/s0102-865020190080000003
|View full text |Cite
|
Sign up to set email alerts
|

Stereological analysis of elastic fibers of the corpus cavernosum of rats during the aging process

Abstract: Purpose To evaluate changes in the quantity of elastic fibers in the corpora cavernosa of rats during the natural aging process, and to assess the degree of this change by determining volumetric density (Vv) at different ages via stereological analysis.Methods Forty-eight rats, raised under similar conditions, were subjected to the natural aging process and divided into four groups (G1 to G4), according to age at the time of penectomy (6, 9, 12, and 24 months, respectively). Histological sections of the middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…20 21 This aging process applies to the penile CC and results in a decline in erectile function. 8 9 10 SWE is a noninvasive method to measure differences in tissue structure, and it is widely used in the differential diagnosis of breast, 22 prostate, 23 and liver 24 diseases. In the current study, we used SWE to evaluate the tissue structure of the CC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 21 This aging process applies to the penile CC and results in a decline in erectile function. 8 9 10 SWE is a noninvasive method to measure differences in tissue structure, and it is widely used in the differential diagnosis of breast, 22 prostate, 23 and liver 24 diseases. In the current study, we used SWE to evaluate the tissue structure of the CC.…”
Section: Discussionmentioning
confidence: 99%
“…Our research confirmed that the CCYM increased with age, and this change was accompanied by a decline in erectile function. It is known that the tissue components of the CC undergo physiological aging, which includes a decrease in smooth muscle mass, a reduction in the expression of elastic fibers, and an increase in collagen content, 8 9 10 25 and these structural changes lead to a decline in erectile function. Because the stiffness of collagen on SWE is higher than that of smooth muscle, 14 15 the increase in collagen content and decrease in smooth muscle content with age might explain the increased CCYM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation